METHOD PROPOSAL FOR DETERMINING URBAN/RURAL LAND VALUE IN URBAN SPRAWL AREA - Özer KARAKAYACI (Fırat University, 2019)
Concept of urban sprawl is described as areas spreading from rural areas to the cities and having low population density, occurring transportation problems, having low social capital. Scientific studies done relating to social, physical, economic and legal dimensions of Urban Sprawl areas which has its own characteristics isn’t evaluated approach with both approaches for rural areas and approaches urban areas. Because of Urban Sprawl areas which has its own characteristics, method of scientific studies concerning about urban sprawl areas which will vary in each region must suitable according to characteristics of the region. Moving from this perspective, the purposes of this study determine a method for determining urban land/rural land value in urban sprawl area. Thus, we have been trying to resolve the issue experiencing in determining the value of urban sprawl areas. Determining of value in urban sprawl areas is including paradox issue made according to method of rural land value or method of urban land value in urban sprawl area in literature. In other words, two methods are used to determine land value in urban sprawl areas. Firstly, the method which is determining the value of agricultural land is used. Secondly, the methods which is determining according to the type of urban use on urban sprawl areas are used. In the first method, land value in urban sprawl areas will be too below of the actual values. In the second method, land value in urban sprawl areas will be relatively high of the actual values. Thus, methods for determining of land value in urban sprawl areas which has its own characteristics is needed. This study; we aimed to develop a method proposal for determining urban land/rural land value in urban sprawl area. Although there are variable which can’t be included in traditional methods such as income method and market method, new methods such as Analytical Hierarchy Processes (AHP) and Grey Relation Analysis (GRA) can be used this variable. As a result, we aimed to develop a method proposal with Analytical Hierarchy Processes (AHP) and Grey Relation Analysis (GRA) for determining the land value in urban sprawl areas in this study.